Purwarupa Monitoring Tandon Air Dan Kontrol Pompa Secara Otomatis Berbasis Internet Of Things - Widodo, Ferry; Mardianto, Eko; Hendro Yuwono, Yohannes Chysostomos (Jurnal ELIT, 2024)
This research develops a prototype of a water supply monitoring and control system utilizing IoT technology that can be implemented in various locations. Water, as a vital resource, is used for a wide range of needs, from household to industrial applications. The system developed uses a WLT sensor to detect water levels connected to a PLC, and an ultrasonic sensor to measure water levels in the tank, which is connected to an ESP32. The data is sent to the Blynk platform, enabling real-time monitoring and control of tank water filling through a mobile application or web PC. The results show that this system is effective in measuring water levels and controlling the pump automatically, preventing water wastage. IoT connectivity via Blynk allows for monitoring and control anytime and anywhere. These findings highlight the importance of IoT technology in enhancing the efficiency of water and electricity usage, offering practical solutions within the academic environment in West Kalimantan.